The Phenomenon of Loan Words That Often Used in Social Media - Helmita, Helmita (Fakultas Sastra Universitas Ekasakti, 2024)
This study uses Sociolinguistics theory, especially regarding the phenomenon of loan words in social media. The purpose of writing is to determine adoption, adaptation and levy from social media. Absorbed words serve to enrich vocabulary and provide more knowledge about foreign languages to Indonesian language users. Because it comes from a foreign language, of course there are some letters that are transliterated into Latin letters in accordance with the rules that apply in Indonesian. This research is descriptive qualitative research, using observation method. This research is what is often confusing when we are going to use absorbing words that are often mistaken in a writing. From this reasearch, the writer found that many words from english that aborbing and people used in social media.